Pendampingan Pembelajaran Kitab Fathul Qarib Bagi Santriwati di Madrasah Diniyah Takmiliyah Al Ma’ruf Kediri - Saparwadi; Solehudin, Muhamad (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Diniyah madrasas have a big role in shaping the character and scientific spirit of their students. With the characteristics, characteristics and typical way of life that takes place as well as a model for character development for students. This research uses several methods in its implementation. Quantity of time can help students achieve understanding. Good communication between students and teachers. Prioritize assignments, make detailed schedules, and stick to the schedule.